2015
DOI: 10.1098/rsta.2014.0174
|View full text |Cite
|
Sign up to set email alerts
|

The alkali metals: 200 years of surprises

Abstract: One contribution of 18 to a discussion meeting issue 'The new chemistry of the elements' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
1
27
0
2
Order By: Relevance
“…These mixtures are highly reactive electron conductors. While there are many reports of dissolving sodium and potassium in cyclic ethers [21][22][23][24] , the possibility of dissolving lithium in ethers has, to our knowledge, not been reported. Additional work is required to establish the properties of lithium metal dissolved in PEO.…”
Section: Main Textmentioning
confidence: 97%
“…These mixtures are highly reactive electron conductors. While there are many reports of dissolving sodium and potassium in cyclic ethers [21][22][23][24] , the possibility of dissolving lithium in ethers has, to our knowledge, not been reported. Additional work is required to establish the properties of lithium metal dissolved in PEO.…”
Section: Main Textmentioning
confidence: 97%
“…Our studies paint a picture of an alkalide species being far beyond a “gaslike” ion in solution, but instead one that could be “chemically” controlled and developed by considering superalkali–alkalide interactions of the sort delineated here. We believe that the interactions of alkalides in solution is merely the most recent in a long line of surprising and unique aspects of s-block chemistry 1 and certainly one that has the potential to affect how these systems are extended and applied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Anionic forms of the electropositive Group I metals, with the exception of lithium, can be generated in condensed phases. 1 Termed alkalides, these monoanions are chemically highly reducing and possess a diffuse, closed-shell n s 2 configuration, resulting in an exceptionally high electronic polarizability. The formation and stabilization of alkalide species requires stringent chemical environments and involves either a disproportionation or the reduction of one elemental alkali metal by another.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we apply PIMC to study sodium. Na is an element that has been of wide interest [9] since it is traditionally viewed as a "simple metal" yet adopts a series of non-close-packed phases under high pressure [10], associated with changes in optical and electronic properties [11,12] and melting behavior [13,14]. It was also found that Na turns insulating at 200 GPa and re-metalizes at 15.5 TPa [15,16,17].…”
Section: Introductionmentioning
confidence: 99%